A heat-resistant high-strength aluminum alloy material and preparation method thereof
By optimizing the chemical composition of aluminum alloy materials and adding modified carbon nanotubes, the problem of insufficient heat resistance at high temperatures is solved, and the effects of high strength, high toughness and excellent heat resistance are achieved, while reducing production costs.
Patent Information
- Application Number
- CN202410048138.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-01-12
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2044-01-12
AI Technical Summary
The existing high-strength aluminum alloy materials have insufficient heat resistance when used at high temperatures. At the same time, their production process is complex and costly, which affects their promotion and application in the ordinary market.
By optimizing the chemical composition of aluminum alloy materials, increasing the amount of Fe, Mg, Co, Mo, Ni and rare earth metals, and adding modified carbon nanotubes to improve the strength and heat resistance of the material. Silicon sol is used to wrap carbon nanotubes and a special mixing and sintering process to improve the performance of the material.
It realizes the high strength, high toughness and excellent heat resistance of aluminum alloy materials, expands its application areas, reduces production costs and improves quality stability.
Smart Images

Figure GDA0005236705140000101
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of aluminum alloys, and in particular relates to a heat-resistant high-strength and toughness aluminum alloy material and a preparation method thereof. Background Art
[0002] Aluminum alloys are widely used in the fields of aerospace and transportation due to their light weight, high strength, corrosion resistance and easy processing. Among them, heat-resistant aluminum-based materials are used to prepare parts that serve at high temperatures, such as pistons, cylinder liners, boxes, missile casings, aircraft engine cylinders, blades, etc., all of which require heat-resistant aluminum-based materials. The rapid development of the aviation, aerospace and automobile industries has put forward higher and higher requirements on the heat resistance of heat-resistant aluminum-based materials. High-strength and toughness aluminum alloy is a kind of aluminum alloy, whose strength can usually reach more than twice that of traditional aluminum alloys, and its tensile strength and yield strength are both over 200MPa, which gives it a high load-bearing capacity. High-strength and toughness aluminum alloy also has good toughness, that is, it is not easy to break when damaged by external forces, but is easy to undergo plastic deformation, which makes it have better processability and performance. Although high-strength and tough aluminum alloys have broad application prospects, they also have disadvantages, such as unstable quality. The production process of high-strength and tough aluminum alloys is relatively complicated. At the same time, its chemical composition and microstructure also have a great influence on its performance. Therefore, the stability of quality is lower than that of traditional aluminum alloys. This requires that various components can play a role in aluminum alloys evenly and stably, and puts forward higher requirements for the mixing of various components. Another disadvantage is that the cost is high. The cost of raw materials required for high-strength and tough aluminum alloys is high. At the same time, its production process is also relatively complicated, making its cost higher than other aluminum alloys or steels. This also limits its promotion and application in the general market. In future processing and application, it is necessary to comprehensively consider its advantages and disadvantages according to the specific situation, and take effective measures to strengthen quality control and improve production processes to promote and develop this new material.
[0003] The heat resistance of aluminum alloy materials refers to the ability to be used at higher temperatures without softening. The main ways to improve the heat resistance of aluminum alloys are solid solution strengthening, excess phase strengthening and grain boundary strengthening. For this purpose, Mo, Ni, Cu, Li, Fe or rare earth elements are often added. The addition of rare earth metals improves the toughness and heat resistance of aluminum alloys while increasing strength, but rare earth elements are very expensive, so it is still necessary to optimize the dosage of various elements and introduce other reinforcements.
[0004] Commonly used aluminum alloy composite reinforcements include alumina, boron carbide, silicon carbide and graphene. Since its discovery in 1991, carbon nanotubes have received widespread attention due to their ultra-high strength, modulus and thermal conductivity, and are considered to be an ideal reinforcement material. Carbon nanotubes are a type of nanomaterial that is relatively light in weight and has a certain special structure. They appear black and have no smell. This material has a very good heat transfer effect, so it can be used as a heat transfer material. Doping some micro-nanotubes in the composite material will greatly improve the thermal conductivity of the composite material and increase its heat resistance.
[0005] Carbon nanotubes have self-lubricating properties, and their uniform distribution in the aluminum matrix is beneficial to reducing the wear rate and friction coefficient of the composite material. However, as the load increases, the carbon nanotubes quickly debond from the aluminum alloy due to the poor wettability of the carbon nanotubes and the aluminum matrix, which leads to weak interface bonding, weakening the lubrication effect, and the composite material also has a large number of subsurface fractures and peeling phenomena. Therefore, the dispersion of carbon nanotubes in the aluminum matrix and the interface bonding state between the two are the two major factors affecting the wear resistance of the composite material.
[0006] In summary, there is an urgent need to develop an aluminum alloy material that can fully exert the functions of various components and solve the interface fusion problem, so that the aluminum alloy can withstand high temperatures while having high strength and high toughness. Summary of the invention
[0007] In view of the shortcomings of the above-mentioned prior art, the present invention has discovered a heat-resistant high-strength and toughness aluminum alloy material and a preparation method thereof through a large number of experiments. The aluminum alloy has high heat resistance, high strength and high toughness, and expands the application field of the aluminum alloy material.
[0008] The objective of the present invention is achieved through the following technical solutions:
[0009] Provided is a heat-resistant high-strength and tough aluminum alloy material, wherein the raw material components of the aluminum alloy are as follows by mass percentage: 0.2-0.7wt% of Fe, 0.5-1.2wt% of Cu, 0.4-0.8wt% of Si, 0.1-0.3wt% of Mn, 0.5-1.5wt% of Mg, 0.2-0.4wt% of Zn, 0.1-0.3wt% of Cr, 0.2-0.3wt% of Ti, 1.5-3wt% of Ni, 0.5-1.0wt% of Co, 0.3-0.8wt% of Mo, 1.0-3.0wt% of rare earth metals, 0.5-2.0wt% of modified carbon nanotubes, and the balance is Al; wherein the particle size of the metal powder other than the modified carbon nanotubes is 30-50μm;
[0010] The rare earth metal is one or more of Sc, La, Ce and Y.
[0011] As a further embodiment, the modified carbon nanotubes are prepared by the following steps:
[0012] (1) placing carbon nanotubes in anhydrous ethanol and dispersing them by ultrasonication to obtain a suspension A;
[0013] (2) Add silica sol to suspension A, continue ultrasonic dispersion for 1 to 2 hours, and then stir at a mechanical stirring rate of 60 to 100 rpm in a 100° C. water bath until uniform, to obtain suspension B;
[0014] (3) The suspension B is allowed to stand for 16 to 24 hours, the upper liquid is removed, and the suspension is dried in the shade at room temperature for 3 to 4 days, and then dried in stages according to the steps of 50°C / 5h, 75°C / 10h, 100°C / 5h, and 120°C / 5h. The suspension is vacuum sintered in stages according to the steps of 200°C / 30min, 400°C / 30min, and 800°C / 180min. The sintering heating rate is 5°C / min. After sintering, the suspension is cooled in the furnace to obtain modified carbon nanotubes.
[0015] Preferably, the carbon nanotubes have a diameter of 10 to 20 nm and a length of 1 to 2 μm.
[0016] Preferably, the particle size of the silica sol is 8 to 20 nm, and the SiO2 content is 20 to 30%.
[0017] Preferably, the mass ratio of carbon nanotubes to silica sol is 1:4-6.
[0018] The present invention also provides a method for preparing a heat-resistant high-strength and tough aluminum alloy material, the specific steps of which are as follows: (1) weighing various component raw materials except the modified carbon nanotubes according to the aluminum alloy raw material ratio, and mixing them to obtain alloy powder;
[0019] (2) placing the alloy powder into a vibrating ball mill with a ball-to-material ratio of 1:1, and vibrating the ball mill at 60 Hz for 1 to 3 hours to obtain a mixed alloy;
[0020] (3) placing the mixed alloy, the modified carbon nanotubes weighed in proportion, and stearic acid into a planetary ball mill with a ball-to-material ratio of 5:1, and ball milling at a speed of 200 rpm for 4 to 8 hours to obtain a mixed powder; the mass ratio of stearic acid to modified carbon nanotubes is 0.5:1;
[0021] (4) The mixed powder is placed in a graphite mold and sintered at a temperature of 600°C and a pressure of 30 MPa in a vacuum of 5 Pa for 30 min to obtain a heat-resistant and high-strength aluminum alloy material.
[0022] As a further embodiment, the modified carbon nanotubes are prepared by the following steps:
[0023] (1) placing carbon nanotubes in anhydrous ethanol and dispersing them by ultrasonication to obtain a suspension A;
[0024] (2) Add silica sol to suspension A, continue ultrasonic dispersion for 1 to 2 hours, and then stir at a mechanical stirring rate of 60 to 100 rpm in a 100° C. water bath until uniform, to obtain suspension B;
[0025] (3) The suspension B is allowed to stand for 16 to 24 hours, the upper liquid is removed, and the suspension is dried in the shade at room temperature for 3 to 4 days, and then dried in stages according to the steps of 50°C / 5h, 75°C / 10h, 100°C / 5h, and 120°C / 5h. The suspension is vacuum sintered in stages according to the steps of 200°C / 30min, 400°C / 30min, and 800°C / 180min. The sintering heating rate is 5°C / min. After sintering, the suspension is cooled in the furnace to obtain modified carbon nanotubes.
[0026] Preferably, the carbon nanotubes have a diameter of 10 to 20 nm and a length of 1 to 2 μm.
[0027] Preferably, the particle size of the silica sol is 8 to 20 nm, and the SiO2 content is 20 to 30%.
[0028] Preferably, the mass ratio of carbon nanotubes to silica sol is 1:4-6.
[0029] The beneficial effects of the present invention are as follows: after a large number of experimental studies, the present invention has selected the alloying elements in the aluminum alloy material and optimized the content of these alloying elements, and designed a special mixing method for the mixing of multi-phase raw materials, with the purpose of providing a high-strength and tough aluminum alloy material with excellent heat resistance. Specifically, one of the advances of the present invention is to appropriately increase the amount of Fe, Mg, Co, Mo, Ni and rare earth metals in the aluminum alloy material, which are beneficial to the strength and heat resistance of the aluminum alloy material, and at the same time, specially add modified carbon nanotubes to further improve the strength and heat resistance of the aluminum alloy material. Another advance of the present invention is to modify the carbon nanotubes, use silica sol to wrap the carbon nanotubes, and by controlling the mixing and sintering process, improve the mutual fusion of the carbon nanotubes and the silicon dioxide in the silica sol, so that when mixed with metal powder later, the carbon nanotubes can play a better and more uniform role. Another improvement of the present invention is that in the preparation of the aluminum alloy material, the metal powder is pre-mixed, that is, the metal powder is mixed in a ball mill with a low ball-to-material ratio and a vibration method, so that the metal powder is mixed evenly but loosely combined, and then when mixed with the modified carbon nanotubes, a high ball-to-material ratio and a higher rotation speed are used to mix, so as to better fuse the two-phase interface between the modified carbon nanotubes and the metal powder. Such a mixing method of the present invention allows the carbon nanotubes to maintain the combination with the metal elements during the subsequent sintering and use of the material, thereby maintaining the performance of the aluminum alloy material. DETAILED DESCRIPTION
[0030] In order to enable those skilled in the art to better understand the technical solution of the present invention, the present invention is described in further detail below.
[0031] In order to make the purpose, technical solution and advantages of the present invention clearer, the technical solution in the embodiment of the present invention is clearly and completely described below. Obviously, the described embodiment is a part of the embodiment of the present invention, not all the embodiments. Based on the embodiment of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work belong to the protection scope of the present invention.
[0032] The particle size of the metal powder used in the embodiment of the present invention is 30-50 μm, and the purity is 99.5%. The diameter of the carbon nanotube is 10-20 nm, and the length is 1-2 μm. The particle size of the silica sol is 10-20 nm, and the SiO2 content is 30%.
[0033] Example 1
[0034] A heat-resistant and high-strength aluminum alloy material of the present embodiment has the following chemical composition, in terms of mass percentage: 0.5wt% Fe, 1.0wt% Cu, 0.6wt% Si, 0.2wt% Mn, 1.0wt% Mg, 0.3wt% Zn, 0.2wt% Cr, 0.2wt% Ti, 2.0wt% Ni, 0.5wt% Co, 0.5wt% Mo, 1.0wt% Sc, 2.0wt% modified carbon nanotubes, and the balance is Al.
[0035] The preparation steps are as follows:
[0036] (1) Preparation of modified carbon nanotubes: 20 g of carbon nanotubes were placed in 100 ml of anhydrous ethanol and ultrasonically dispersed at an ultrasonic frequency of 50 kHz to obtain suspension A; 100 g of silica sol was added to suspension A and ultrasonic dispersion was continued for 1.5 h, followed by stirring at a mechanical stirring rate of 100 rpm in a 100°C water bath until uniform to obtain suspension B; suspension B was allowed to stand for 16 h, the upper liquid was removed, and the suspension was dried in the shade at room temperature for 3 days, then dried in stages at 50°C / 5 h, 75°C / 10 h, 100°C / 5 h, and 120°C / 5 h, and vacuum sintered in stages at 200°C / 30 min, 400°C / 30 min, and 800°C / 180 min, with the sintering heating rate being 5°C / min. After sintering, the suspension was cooled in the furnace to obtain modified carbon nanotubes.
[0037] (2) Weighing each component raw material except the modified carbon nanotubes according to the ratio of the aluminum alloy raw materials, and mixing to obtain 98 g of alloy powder;
[0038] (3) placing the alloy powder into a vibrating ball mill with a ball-to-material ratio of 1:1, and vibrating the ball mill at 60 Hz for 2 h to obtain a mixed alloy;
[0039] (4) The mixed alloy, 2 g of modified carbon nanotubes, and 1 g of stearic acid were placed in a planetary ball mill with a ball-to-material ratio of 5:1, and ball milled at a speed of 200 rpm for 6 h to obtain a mixed powder;
[0040] (5) The mixed powder is placed in a graphite mold and sintered at a temperature of 600°C and a pressure of 30 MPa in a vacuum of 5 Pa for 30 min to obtain a heat-resistant and high-strength aluminum alloy material.
[0041] Example 2
[0042] A heat-resistant, high-strength and tough aluminum alloy material of the present embodiment has the following chemical composition, in terms of mass percentage: 0.6wt% Fe, 1.0wt% Cu, 0.8wt% Si, 0.3wt% Mn, 1.2wt% Mg, 0.4wt% Zn, 0.3wt% Cr, 0.2wt% Ti, 1.5wt% Ni, 0.5wt% Co, 0.6wt% Mo, 1.5wt% La, 2.0wt% modified carbon nanotubes, and the balance is Al.
[0043] The preparation steps are as follows:
[0044] (1) Preparation of modified carbon nanotubes: 20 g of carbon nanotubes were placed in 100 ml of anhydrous ethanol and ultrasonically dispersed at an ultrasonic frequency of 50 kHz to obtain suspension A; 80 g of silica sol was added to suspension A, and ultrasonic dispersion was continued for 1 hour, followed by stirring at a mechanical stirring rate of 90 rpm under 100°C water bath heating until uniform, to obtain suspension B; suspension B was allowed to stand for 20 hours, the upper liquid was removed, and it was dried in the shade at room temperature for 3 days, and then dried in stages according to the steps of 50°C / 5h, 75°C / 10h, 100°C / 5h, and 120°C / 5h, and vacuum sintered in stages according to the steps of 200°C / 30min, 400°C / 30min, and 800°C / 180min, with the sintering heating rate being 5°C / min. After sintering, it was cooled in the furnace to obtain modified carbon nanotubes.
[0045] (2) Weighing each component raw material except the modified carbon nanotubes according to the ratio of the aluminum alloy raw materials, and mixing to obtain 98 g of alloy powder;
[0046] (3) placing the alloy powder into a vibrating ball mill with a ball-to-material ratio of 1:1, and vibrating the ball mill at 60 Hz for 3 h to obtain a mixed alloy;
[0047] (4) The mixed alloy, 2 g of modified carbon nanotubes, and 1 g of stearic acid were placed in a planetary ball mill with a ball-to-material ratio of 5:1, and ball milled at a speed of 200 rpm for 6 h to obtain a mixed powder;
[0048] (5) The mixed powder is placed in a graphite mold and sintered at a temperature of 600°C and a pressure of 30 MPa in a vacuum of 5 Pa for 30 min to obtain a heat-resistant and high-strength aluminum alloy material.
[0049] Example 3
[0050] A heat-resistant, high-strength and tough aluminum alloy material of the present embodiment has the following chemical composition, in terms of mass percentage: 0.5wt% Fe, 1.0wt% Cu, 0.6wt% Si, 0.2wt% Mn, 1.0wt% Mg, 0.3wt% Zn, 0.2wt% Cr, 0.2wt% Ti, 2.0wt% Ni, 0.5wt% Co, 0.5wt% Mo, 1.0wt% Sc, 1.5wt% modified carbon nanotubes, and the balance is Al.
[0051] The preparation steps are as follows:
[0052] (1) Preparation of modified carbon nanotubes: 20 g of carbon nanotubes were placed in 100 ml of anhydrous ethanol and ultrasonically dispersed at an ultrasonic frequency of 50 kHz to obtain suspension A; 120 g of silica sol was added to suspension A and ultrasonic dispersion was continued for 2 h, followed by stirring at a mechanical stirring rate of 100 rpm in a 100°C water bath until uniform, to obtain suspension B; suspension B was allowed to stand for 20 h, the upper liquid was removed, and the suspension was dried in the shade at room temperature for 4 days, then dried in stages at 50°C / 5 h, 75°C / 10 h, 100°C / 5 h, and 120°C / 5 h, and vacuum sintered in stages at 200°C / 30 min, 400°C / 30 min, and 800°C / 180 min, with the sintering heating rate being 5°C / min. After sintering, the suspension was cooled in the furnace to obtain modified carbon nanotubes.
[0053] (2) Weighing each component raw material except the modified carbon nanotubes according to the aluminum alloy raw material ratio, and mixing to obtain 98.5 g of alloy powder;
[0054] (3) placing the alloy powder into a vibrating ball mill with a ball-to-material ratio of 1:1, and vibrating the ball mill at 60 Hz for 2 h to obtain a mixed alloy;
[0055] (4) The mixed alloy, 1.5 g of modified carbon nanotubes, and 0.75 g of stearic acid were placed in a planetary ball mill (ball-to-material ratio 5:1), and ball milled at a speed of 200 rpm for 8 h to obtain a mixed powder;
[0056] (5) The mixed powder is placed in a graphite mold and sintered at a temperature of 600°C and a pressure of 30 MPa in a vacuum of 5 Pa for 30 min to obtain a heat-resistant and high-strength aluminum alloy material.
[0057] Example 4
[0058] A heat-resistant and high-strength aluminum alloy material of the present embodiment, in terms of mass percentage, the chemical composition of the aluminum alloy is as follows: 0.4wt% Fe, 1.2wt% Cu, 0.8wt% Si, 0.1wt% Mn, 0.5wt% Mg, 0.2wt% Zn, 0.3wt% Cr, 0.3wt% Ti, 3.0wt% Ni, 1.0wt% Co, 0.7wt% Mo, 3.0wt% Ce, 1.0wt% modified carbon nanotubes, and the balance is Al.
[0059] The preparation steps are as follows:
[0060] (1) Preparation of modified carbon nanotubes: 20 g of carbon nanotubes were placed in 100 ml of anhydrous ethanol and ultrasonically dispersed at an ultrasonic frequency of 50 kHz to obtain suspension A; 100 g of silica sol was added to suspension A and ultrasonic dispersion was continued for 1.5 h, followed by stirring at a mechanical stirring rate of 100 rpm in a 100°C water bath until uniform to obtain suspension B; suspension B was allowed to stand for 16 h, the upper liquid was removed, and the suspension was dried in the shade at room temperature for 3 days, then dried in stages at 50°C / 5 h, 75°C / 10 h, 100°C / 5 h, and 120°C / 5 h, and vacuum sintered in stages at 200°C / 30 min, 400°C / 30 min, and 800°C / 180 min, with the sintering heating rate being 5°C / min. After sintering, the suspension was cooled in the furnace to obtain modified carbon nanotubes.
[0061] (2) Weighing all raw materials except the modified carbon nanotubes according to the ratio of the aluminum alloy raw materials, and mixing them to obtain 99 g of alloy powder;
[0062] (3) placing the alloy powder into a vibrating ball mill with a ball-to-material ratio of 1:1, and vibrating the ball mill at 60 Hz for 2 h to obtain a mixed alloy;
[0063] (4) The mixed alloy, 1 g of modified carbon nanotubes, and 0.5 g of stearic acid were placed in a planetary ball mill (ball-to-material ratio 5:1), and ball milled at a speed of 200 rpm for 4 h to obtain a mixed powder;
[0064] (5) The mixed powder is placed in a graphite mold and sintered at a temperature of 600°C and a pressure of 30 MPa in a vacuum of 5 Pa for 30 min to obtain a heat-resistant and high-strength aluminum alloy material.
[0065] Comparative Example 1
[0066] A heat-resistant and high-strength and tough aluminum alloy material in this comparative example has a chemical composition, in terms of mass percentage, as follows: 0.6wt% Fe, 1.0wt% Cu, 0.8wt% Si, 0.3wt% Mn, 1.2wt% Mg, 0.4wt% Zn, 0.3wt% Cr, 0.2wt% Ti, 0.5wt% Ni, 0.5wt% Co, 0.6wt% Mo, 1.5wt% La, and the balance is Al.
[0067] The preparation steps are as follows:
[0068] (1) Weigh the raw materials of each component according to the ratio of the aluminum alloy raw materials, and mix them to obtain 100 g of alloy powder;
[0069] (2) placing the alloy powder into a vibrating ball mill with a ball-to-material ratio of 1:1, and vibrating the ball mill at 60 Hz for 3 h to obtain a mixed alloy;
[0070] (3) The alloy powder is placed in a graphite mold and sintered at a temperature of 600°C and a pressure of 30 MPa in a vacuum of 5 Pa for 30 min to obtain a heat-resistant and high-strength aluminum alloy material.
[0071] Comparative Example 2
[0072] A heat-resistant and high-strength and tough aluminum alloy material in this comparative example has the following chemical composition, in terms of mass percentage: 0.4wt% Fe, 1.2wt% Cu, 0.8wt% Si, 0.1wt% Mn, 0.5wt% Mg, 0.2wt% Zn, 0.3wt% Cr, 0.3wt% Ti, 1.0wt% Ni, 1.0wt% Co, 0.7wt% Mo, 2.0wt% Ce, 1.0wt% carbon nanotubes, and the balance is Al.
[0073] The preparation steps are as follows:
[0074] (1) Weighing all raw materials except carbon nanotubes according to the ratio of aluminum alloy raw materials, and mixing to obtain 99 g of alloy powder;
[0075] (2) The alloy powder, 1 g of carbon nanotubes, and 0.5 g of stearic acid were placed in a planetary ball mill with a ball-to-material ratio of 5:1, and ball milled at a speed of 200 rpm for 4 h to obtain a mixed powder;
[0076] (3) The mixed powder is placed in a graphite mold and sintered at a temperature of 600°C and a pressure of 30 MPa in a vacuum of 5 Pa for 30 min to obtain a heat-resistant and high-strength aluminum alloy material.
[0077] Comparative Example 3
[0078] A heat-resistant and high-strength and tough aluminum alloy material in this comparative example has the following chemical composition, in terms of mass percentage: 0.5wt% Fe, 1.0wt% Cu, 0.6wt% Si, 0.2wt% Mn, 1.0wt% Mg, 0.3wt% Zn, 0.2wt% Cr, 0.2wt% Ti, 0.5wt% Co, 0.5wt% Mo, 1.5wt% modified carbon nanotubes, and the balance is Al.
[0079] The preparation steps are as follows:
[0080] (1) Preparation of modified carbon nanotubes: 20 g of carbon nanotubes were placed in 100 ml of anhydrous ethanol and ultrasonically dispersed at an ultrasonic frequency of 50 kHz to obtain suspension A; 60 g of silica sol was added to suspension A and ultrasonic dispersion was continued for 1.5 h, followed by stirring at a mechanical stirring rate of 100 rpm in a 100°C water bath until uniform to obtain suspension B; suspension B was allowed to stand for 16 h, the upper liquid was removed, and the suspension was dried in the shade at room temperature for 3 days, then dried in stages at 50°C / 5 h, 75°C / 10 h, 100°C / 5 h, and 120°C / 5 h, and vacuum sintered in stages at 200°C / 30 min, 400°C / 30 min, and 800°C / 180 min, with the sintering heating rate being 5°C / min. After sintering, the suspension was cooled in the furnace to obtain modified carbon nanotubes.
[0081] (2) Weighing each component raw material except the modified carbon nanotubes according to the aluminum alloy raw material ratio, and mixing to obtain 98.5 g of alloy powder;
[0082] (3) placing the alloy powder and 1.5 g of modified carbon nanotubes into a vibrating ball mill with a ball-to-material ratio of 1:1, and vibrating the ball mill at 60 Hz for 6 h to obtain a mixed powder;
[0083] (4) The mixed powder is placed in a graphite mold and sintered at a temperature of 600°C and a pressure of 30 MPa in a vacuum of 5 Pa for 30 min to obtain a heat-resistant and high-strength aluminum alloy material.
[0084] The aluminum alloy materials prepared in the above embodiments and comparative examples were subjected to performance tests, and the test method was: testing tensile strength, yield strength and elongation after fracture according to standard GB / T 228.1-2010, wherein the elongation after fracture indicates the toughness of the aluminum alloy material when subjected to external force impact. The test results are shown in Table 1.
[0085] Table 1 Test results of aluminum alloy materials
[0086]
[0087] It can be seen from Table 1 that the aluminum alloy material obtained in the embodiment has significantly higher room temperature tensile strength, yield strength and elongation than the aluminum alloy material obtained in the comparative example, which indicates that the aluminum alloy material obtained in the present invention is a high-strength and tough aluminum alloy. The heat resistance test results show that after accelerated aging at 200°C and 400h, the aluminum alloy material obtained in the present invention can still reach a tensile strength of more than 320MPa, a yield strength of more than 200MPa and an elongation of 9-11%, and has excellent heat resistance. The contents of Ni, Co, Mo, Cu and rare earth metals in Example 4 are relatively high, so it is superior to other embodiments in terms of room temperature strength, toughness and heat resistance.
[0088] Comparative Example 1 did not add modified carbon nanotubes, Comparative Example 2 added unmodified carbon nanotubes and did not pre-mix metal powders, and Comparative Example 3 did not add rare earth elements and did not pre-mix metal powders; when mixing the modified carbon nanotubes, stearic acid was not added and an appropriate ball milling ratio was not used. These all affected the tensile strength, yield strength and elongation after fracture, and also affected the heat resistance.
[0089] Each embodiment in this specification is described in a related manner, and the same or similar parts between the embodiments can be referred to each other, and each embodiment focuses on the differences from other embodiments. In particular, for the system embodiment, since it is basically similar to the method embodiment, the description is relatively simple, and the relevant parts can be referred to the partial description of the method embodiment.
[0090] The above description is only a preferred embodiment of the present invention and is not intended to limit the protection scope of the present invention. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention are included in the protection scope of the present invention.
Claims
1. A heat-resistant, high-strength and tough aluminum alloy material, characterized in that: The raw material components of the aluminum alloy are as follows by mass percentage: 0.2~0.7wt%Fe, 0.5~1.2wt%Cu, 0.4-0.8wt% Si, 0.1~0.3wt% Mn, 0.5-1.5wt% Mg, 0.2-0.4wt% Zn, 0.1~0.3wt% Cr, 0.2-0.3wt% Ti, 1.5~3wt% Ni, 0.5~1.0wt% Co, 0.3~0.8wt% Mo, 1.0~3.0wt% rare earth metal, 0.5-2.0wt% of modified carbon nanotubes, The balance is Al; The particle size of the metal powder except the modified carbon nanotubes is 30 to 50 μm; The rare earth metal is one or more of Sc, La, Ce and Y; The modified carbon nanotubes are prepared by the following steps: (1) placing carbon nanotubes in anhydrous ethanol and dispersing them by ultrasonication to obtain a suspension A; (2) Add silica sol to suspension A, continue ultrasonic dispersion for 1 to 2 hours, and then stir at a mechanical stirring rate of 60 to 100 rpm in a 100° C. water bath until uniform, to obtain suspension B; (3) The suspension B is allowed to stand for 16 to 24 hours, the upper liquid is removed, and the suspension is dried in the shade at room temperature for 3 to 4 days, and then dried in stages according to the steps of 50°C / 5h, 75°C / 10h, 100°C / 5h, and 120°C / 5h. The suspension is vacuum sintered in stages according to the steps of 200°C / 30min, 400°C / 30min, and 800°C / 180min. The sintering heating rate is 5°C / min. After sintering, the suspension is cooled in the furnace to obtain modified carbon nanotubes.
2. The heat-resistant high-strength and tough aluminum alloy material according to claim 1, characterized in that: The diameter of carbon nanotubes is 10 to 20 nm and the length is 1 to 2 μm.
3. The heat-resistant high-strength and tough aluminum alloy material according to claim 1, characterized in that: The particle size of the silica sol is 8 to 20 nm, and the SiO2 content is 20 to 30%.
4. The heat-resistant high-strength and tough aluminum alloy material according to claim 1, characterized in that: The mass ratio of carbon nanotubes to silica sol is 1:4-6.
5. A method for preparing an aluminum alloy material according to any one of claims 1 to 4, characterized in that: The following steps are involved: (1) weighing various raw materials except the modified carbon nanotubes according to the ratio of the aluminum alloy raw materials, and mixing them to obtain alloy powder; (2) placing the alloy powder into a vibrating ball mill with a ball-to-material ratio of 1:1, and vibrating the ball mill at 60 Hz for 1 to 3 hours to obtain a mixed alloy; (3) placing the mixed alloy, the modified carbon nanotubes weighed in proportion, and stearic acid into a planetary ball mill with a ball-to-material ratio of 5:1, and ball milling at a speed of 200 rpm for 4 to 8 hours to obtain a mixed powder; the mass ratio of stearic acid to modified carbon nanotubes is 0.5:1; (4) The mixed powder is placed in a graphite mold and sintered at a temperature of 600° C. and a pressure of 30 MPa in a vacuum of 5 Pa for 30 min to obtain a heat-resistant, high-strength and tough aluminum alloy material; The modified carbon nanotubes are prepared by the following steps: (1) placing carbon nanotubes in anhydrous ethanol and dispersing them by ultrasonication to obtain a suspension A; (2) Add silica sol to suspension A, continue ultrasonic dispersion for 1 to 2 hours, and then stir at a mechanical stirring rate of 60 to 100 rpm in a 100° C. water bath until uniform, to obtain suspension B; (3) The suspension B is allowed to stand for 16 to 24 hours, the upper liquid is removed, and the suspension is dried in the shade at room temperature for 3 to 4 days, and then dried in stages according to the steps of 50°C / 5h, 75°C / 10h, 100°C / 5h, and 120°C / 5h. The suspension is vacuum sintered in stages according to the steps of 200°C / 30min, 400°C / 30min, and 800°C / 180min. The sintering heating rate is 5°C / min. After sintering, the suspension is cooled in the furnace to obtain modified carbon nanotubes.
6. The method for preparing the aluminum alloy material according to claim 5, characterized in that: The diameter of carbon nanotubes is 10 to 20 nm and the length is 1 to 2 μm.
7. The method for preparing the alloy material according to claim 5, characterized in that: The particle size of the silica sol is 8 to 20 nm, and the SiO2 content is 20 to 30%.
8. The method for preparing the aluminum alloy material according to claim 5, characterized in that: The mass ratio of carbon nanotubes to silica sol is 1:4-6.
Citation Information
Patent Citations
Carbon-nanotube-reinforced aluminum-base composite material
CN103602843A